Rola nauczyciela wiedzy o społeczeństwie w obecnej edukacji szkolnej w Polsce - Dutka, Wojciech (Kultura-Społeczeństwo-Edukacja, 2023)
The subject Civics (Social Knowledge) in outgoing school year 2023/2024 was replaced subject History and Present in standard level in Polish middle schools system. The role of Social Knowledge was reduced to higher level only. The decision of Polish Ministry of Education in school year 2021/2022 brings important implications in area of didactics, but also provides the consequences in culture, philosophy of school and ethics of teachers. The article first discusses the issue of modernity as a key concept for understanding the diagnosis of teaching Social Studies. Then the author tries to describe the teacher as a guide in postmodernity, however it refers to the philosophical concept of Hans-Georg Gadamer “historian as translator”. The author points out that when teaching Social Studies, it is important for the teacher to apply Pyrrho’s principle of epoche, i.e. suspension of one’s own views. Only in this way can the school become a place of dialogue. Knowledge about society appears to be an essential element of young people’s understanding of modern times based on the complexity of the world. The article describes this matter from point of view of philosophy and theory of didactics. The role of Civics (Social Knowledge) was brought to be important in building the civil society. Article shows the discussion and indicates some practical explanations.